DOI: 10.31274/etd-180810-2024
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the enrollment and academic success of dual credit and non-dual credit students at Des Moines Area Community College

Abstract: Iowa has embraced joint enrollment with their secondary and postsecondary institutions. Legislated incentives have been created in Iowa which involve creating joint enrollment opportunities for students between the secondary schools and Iowa's 15 community colleges whose boundaries determine which school districts they are to partner with. Similar boundaries exist for Iowa's Area Education Agencies which coincide with the community colleges. The Area Education Agencies are the regional agencies set up in Iowa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Students may get a head start on preparing for the more difficult courses encountered in the collegiate setting. Many researchers are finding results that show students who participate in dual enrollment persist at higher rates, ease transition, are more college ready, earn high college GPAs, and have a higher rate of degree attainment Fara, 2010;Fink, et al, 2017Iowa Department of Education, 2014aMead, 2009;Noble & Wheeler, 2014;Radunzel,).…”
Section: Statement Of Problemmentioning
confidence: 99%
See 4 more Smart Citations
“…Students may get a head start on preparing for the more difficult courses encountered in the collegiate setting. Many researchers are finding results that show students who participate in dual enrollment persist at higher rates, ease transition, are more college ready, earn high college GPAs, and have a higher rate of degree attainment Fara, 2010;Fink, et al, 2017Iowa Department of Education, 2014aMead, 2009;Noble & Wheeler, 2014;Radunzel,).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Several researchers have concluded in the results of their studies that students who participate in dual enrollment persist at higher rates, ease transition from secondary to postsecondary education, are more college ready, earn high college GPAs, and have a higher rate of degree attainment Fara, 2010;Iowa Department of Education, 2014a;Mead, 2009;Radunzel, Noble & Wheeler, 2014). Findings have also revealed that dual credit aids in the transition and preparedness into the university setting; therefore, it is important to identify which factors, in addition to early credit, lead to positive reports of academic selfefficacy and academic resiliency Callan, et.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 3 more Smart Citations